Simulasi Distribusi Tegangan Sisa Dalam Proses Pengelasan Plat Dengan Metode Elemen Hingga - Utaja Utaja; B. Bandriyana B. Bandriyana (Jurnal Perangkat Nuklir, 2007)
Simulation of Residual Stress Distribution on Welding Process For Plate Using Finite Element Method. Simulation and modeling were performed to calculate the residual stress on plate welding. The calculation was carried out on the 3 kinds of butt welding types of I, V and Y type. The steel plate St E460 with 16 mm thick, and the welding material standard with the heat conductivity of k = 12 x106 WI °K.m2 and thermal expansion of a = 1 Ox1 0-6 mm/mm were used as a model. The residual stress was calculated by iteration of the strain which was obtained from the temperature distribution during the cooling process on the welding temperature of 25000C to the room temperature by the transient calculation model. The calculation was done by the finite element method using the 2 dimension modeling of ANSYS 5.4. program. The stress distribution showed the residual stress on the welded area was 100 to 550 MPa, depends on the welded junction type.  Simulasi dan pemodelan dilakukan untuk menghitung distribusi tegangan sisa dalam proses pengelasan pelat. Perhitungan dilakukan untuk 3 macam tipe sambungan tumpu (butt welded joint) yaitu tipe I, tipe V dan tipe Y. Untuk model perhitungan ditentukan pelat dari baja St E460 dengan tebal sama 16 mm, sedangkan material standard las dengan data koefisien konduksi panas, k = 12 x106 WI °K.m2, dan angka muai termal, a = 10 x10-6 mm/mm. Tegangan sisa dihitung berdasarkan iterasi regangan yang timbul akibat distribusi suhu selama pendinginan dari suhu pengelasan sebesar 2500°C menuju temperatur ruang dengan model perhitungan kondisi transient. Perhitungan berdasarkan metode elemen hingga dengan program ANSYS 5.4. model 2 dimensi. Distribusi tegangan menunjukkan harga tegangan total pad a bahan las berkisar antara 100 sampai dengan 550 MPa, bergantung pada tipe sambungan las